2020
DOI: 10.1016/j.isci.2020.101850
|View full text |Cite
|
Sign up to set email alerts
|

Population-Matched Transcriptome Prediction Increases TWAS Discovery and Replication Rate

Abstract: Most genome-wide association studies (GWAS) and transcriptome-wide association studies (TWAS) focus on European populations; however, these results cannot always be accurately applied to non-European populations due to genetic architecture differences. Using GWAS summary statistics in the Population Architecture using Genomics and Epidemiology study, which comprises $50,000 Hispanic/Latinos, African Americans, Asians, Native Hawaiians, and Native Americans, we perform TWAS to determine gene-trait associations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 59 publications
3
23
0
Order By: Relevance
“…Previous work has also suggested the value of ancestry-matched TWAS reference panels. Recent work from Geoffroy, et al [ 24 ] found more significant complex trait-associated genes in summary statistics from the diverse PAGE consortium (~50,000 HL, African American, Asian, Native Hawaiian, and Native American individuals) using models trained in African American and HL MESA participants than in European- or all-ancestry TWAS models. Work in the diverse Carolina Breast Cancer Study (CBCS) cohort also suggests that TWAS models perform poorly across race/ethnicity groups, with multiple novel discoveries for breast cancer survival found in AA women using TWAS gene expression models trained in a subset of the cohort with measured expression data [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has also suggested the value of ancestry-matched TWAS reference panels. Recent work from Geoffroy, et al [ 24 ] found more significant complex trait-associated genes in summary statistics from the diverse PAGE consortium (~50,000 HL, African American, Asian, Native Hawaiian, and Native American individuals) using models trained in African American and HL MESA participants than in European- or all-ancestry TWAS models. Work in the diverse Carolina Breast Cancer Study (CBCS) cohort also suggests that TWAS models perform poorly across race/ethnicity groups, with multiple novel discoveries for breast cancer survival found in AA women using TWAS gene expression models trained in a subset of the cohort with measured expression data [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcripts whose levels can be confidently imputed from genetic variants are then assessed for phenotype associations [ 17 ]. However, like GWAS, TWAS analyses have often included only EA populations [ 18 , 19 ], though some recent efforts have included more diverse populations [ 20 , 21 , 22 , 23 , 24 ]. Furthermore, most reference eQTL datasets used for TWAS include predominantly EA American individuals [ 25 , 26 ], limiting the predictive power of this novel method in other populations with different allele frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has also suggested the value of ancestry-matched TWAS reference panels. Recent work from Geoffroy, et al, [22] found more significant complex trait-associated genes in summary statistics from the diverse PAGE consortium (~50,000 HL, African American, Asian, Native Hawaiian, and Native American individuals) using models trained in African American and HL MESA participants than in European-or all-ancestry TWAS models. Work in the diverse Carolina Breast Cancer Study (CBCS) cohort also suggests that TWAS models perform poorly across race/ethnicity groups, with multiple novel discoveries for breast cancer survival found in AA women using TWAS gene expression models trained in a subset of the cohort with measured expression data [19].…”
Section: Discussionmentioning
confidence: 99%
“…Transcripts whose levels can be confidently imputed from genetic variants are then assessed for phenotype associations [15]. However, like GWAS, TWAS analyses have often included only EA populations [16,17], though some recent efforts have included more diverse populations [18][19][20][21][22]. Furthermore, most reference eQTL datasets used for TWAS include predominantly EA American individuals [23,24], limiting the predictive power of this novel method in other populations with different allele frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these strategies build predictors using single‐tissue expression reference panes, and others use multiple‐tissue panels (Barbeira et al, 2019, 2020; Feng et al, 2021; Hu et al, 2019). TWAS methods have also been extended to account for confounding due to colocalization or pleiotropy or differences in expression prediction across ethnicity (Barfield et al, 2018; Bhattacharya et al, 2020; Geoffroy et al, 2020; L. Liu et al, 2021; Mancuso et al, 2019; Mogil et al, 2018). As we discuss further below, several approaches to multitrait TWAS have recently been proposed (Baselmans et al, 2019; L. Liu et al, 2021; Nagpal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%